2020
DOI: 10.12688/f1000research.26281.2
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic injuries in Nepal during COVID-19 lockdown

Abstract: Background: As the world is busy addressing COVID-19, road traffic injuries, another major cause of deaths is continuously killing people on the roads. In Nepal, there were frequent media reports of occurrences of road crashes, injuries, and deaths despite nationwide lockdown. This paper aims to describe the situation of road traffic crashes and casualties during the period of complete lockdown. Methods: This study used secondary data from two sources: Nepal Police and media reports between 24 March and 14 Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…20 Another unique finding from our study was a 50% increase in motorcycle collisions in male patients during the initial wave. Although no such findings have been demonstrated so far in the literature, 21,22 this trend was consistent with data from our area. 23,24 A report from the Institute for Traffic Safety Management and Research demonstrated that fatal motorcycle accidents in New York State increased more than 30% in 2020 compared to 2019 despite a decrease in road traffic.…”
Section: Discussionsupporting
confidence: 93%
“…20 Another unique finding from our study was a 50% increase in motorcycle collisions in male patients during the initial wave. Although no such findings have been demonstrated so far in the literature, 21,22 this trend was consistent with data from our area. 23,24 A report from the Institute for Traffic Safety Management and Research demonstrated that fatal motorcycle accidents in New York State increased more than 30% in 2020 compared to 2019 despite a decrease in road traffic.…”
Section: Discussionsupporting
confidence: 93%
“…Excessive speed, which is anticipated to increase the incidence and severity of RTCs [ 12 ], has occurred during the COVID-19 pandemic [ 20 , 56 – 61 ]. This was attributed to the significant reduction in traffic volumes and empty roads [ 42 , 44 , 58 , 59 , 62 , 63 ] which encouraged high speeding [ 20 , 42 , 47 , 56 , 57 , 60 , 64 ], and resulted in more RTCs despite the few numbers of vehicles [ 56 , 60 ]. Furthermore, traffic speed enforcement was less [ 20 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the speed-related vehicle collisions decreased in Minnesota (USA) and the Czech Republic despite reduced traffic volumes during lockdown [ 23 , 44 ]. In Nepal, 25% of the RTCs were attributed to speeding during the pandemic [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations